A gene subset requires CTCF bookmarking during the fast post‐mitotic reactivation of mouse ES cells. (4th November 2022) - Chervova, Almira; Festuccia, Nicola; Altamirano‐Pacheco, Luis; Dubois, Agnès; Navarro, Pablo
Abstract: Mitosis leads to global downregulation of transcription that then needs to be efficiently resumed. In somatic cells, this is mediated by a transient hyper‐active state that first reactivates housekeeping and then cell identity genes. Here, we show that mouse embryonic stem cells, which display rapid cell cycles and spend little time in G1, also display accelerated reactivation dynamics. This uniquely fast global reactivation lacks specificity towards functional gene families, enabling the restoration of all regulatory functions before DNA replication. Genes displaying the fastest reactivation are bound by CTCF, a mitotic bookmarking transcription factor. In spite of this, the post‐mitotic global burst is robust and largely insensitive to CTCF depletion. There are, however, around 350 genes that respond to CTCF depletion rapidly after mitotic exit. Remarkably, these are characterised by promoter‐proximal mitotic bookmarking by CTCF. We propose that the structure of the cell cycle imposes distinct constrains to post‐mitotic gene reactivation dynamics in different cell types, via mechanisms that are yet to be identified but that can be modulated by mitotic bookmarking factors. Synopsis: Mouse ES cells exhibit fast global reactivation of their genes following mitosis to restore their regulatory functions before DNA replication. Around 350 genes require the mitotic bookmarking factor CTCF for this process. Mouse ES cells undergo fast and global reactivation of their genes following mitosis. This post‐mitotic reactivation is robust and largely independent of CTCF depletion. However, around 350 genes respond to CTCF depletion. These genes are characterised by promoter‐proximal mitotic bookmarking by CTCF. Abstract : Mouse ES cells exhibit fast global reactivation of their genes following mitosis to restore their regulatory functions before DNA replication. Around 350 genes require the mitotic bookmarking factor CTCF for this process.